In-situ alloying brazing repair method for surface defects of high-temperature alloy blade
By using a mixture of Ni-Cr-Si low-melting-point alloy powder and high-temperature alloy base powder, in-situ alloying brazing repair of surface defects in high-temperature alloys is achieved. This solves the problems of poor high-temperature mechanical properties in brazed repair areas and long homogenization time of instantaneous liquid phase diffusion welding components, achieving efficient and rapid repair results.
Patent Information
- Application Number
- CN202511323057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-09
AI Technical Summary
Among the existing methods for repairing surface defects in high-temperature alloys, brazing-type repairs result in poor high-temperature mechanical properties, while instantaneous liquid phase diffusion welding repairs have a long homogenization time, and the presence of boron in the repair material leads to borides that affect performance.
The Ni-Cr-Si low-melting-point alloy powder is mixed with high-temperature alloy base powder as the repair material. Under vacuum and pressureless conditions, the mixture is heated to a temperature higher than the liquidus line of the Ni-Cr-Si alloy but lower than the solidus line of the base powder. The liquid Ni-Cr-Si alloy wets the high-temperature alloy base material and fills the defect gaps, thereby achieving isothermal liquid-solid diffusion and in-situ alloying brazing repair.
The composition of the repair area is similar to that of the base material, with high heat resistance, good high-temperature mechanical properties, good compositional uniformity, and short repair time, making it suitable for repairing defects ranging from small to large sizes.
Smart Images

Figure CN121083004A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of engine high-temperature alloy blade surface defect repair, in particular, a brazing type repair method is provided, which uses a mixed powder of Ni-Cr-Si low-melting alloy powder and high-temperature alloy base material powder as a repair material, and completes the repair of high-temperature alloy surface cracks, etch pits and other defects by in-situ alloying of the repair material. BACKGROUND
[0002] With the continuous rise of the thrust-to-weight ratio of aero-engines, the turbine inlet temperature is constantly breaking the upper limit. Engine blades including single-crystal high-temperature alloys and cobalt-based high-temperature alloys are prone to defects such as cracks and etch pits under the coupling action of extreme thermal fatigue and hot corrosion, resulting in a sharp drop in mechanical properties or even fracture failure. However, the internal channels of such blades are complex, the materials are rare and valuable (especially single-crystal high-temperature alloys), the casting cycle is long and the yield is low. If the damaged parts are directly scrapped, not only will it cause a huge waste of materials, but also it will significantly increase the operation and maintenance costs of the engine. Therefore, developing efficient and reliable remanufacturing repair can significantly extend the service life of turbine blades, save strategic resources, and greatly reduce the life cycle cost, which has great practical significance for improving the support capability of national defense equipment.
[0003] The surface defects of high-temperature alloy blades are a kind of local damage, which are usually repaired by welding methods. At present, the main methods for repairing high-temperature alloy surface defects are TIG welding, electron beam welding, laser melting / cladding, brazing, and transient liquid phase diffusion welding. The repair area of fusion welding methods (such as TIG welding, electron beam welding, and laser melting / cladding) is prone to appear mixed crystals and cracks, which leads to repair failure. The brazing method usually uses traditional filler metal as repair material, and the repair temperature is relatively low, but the composition of the repair area is quite different from that of the high-temperature alloy base material, and its high-temperature performance is poor. The transient liquid phase diffusion welding method realizes the composition homogenization of the repair area through long-time isothermal diffusion between the repair material and the high-temperature alloy base material, so the high-temperature mechanical properties of the repair area are improved. However, the low-melting filler containing B element is usually used as the repair material in the transient liquid phase diffusion welding repair, and the solid solubility of B element in the Ni matrix is very small, which will lead to the precipitation of a large amount of low-melting-point borides in the repair area, affecting the mechanical properties. These borides generally need a long time of diffusion homogenization to eliminate. For example, X. B. HU et al. used Ni 15Cr 3.5B powder as an intermediate layer material to connect certain single crystal superalloys [Hu X B, et al. Metall. Mater. Trans. A, 2020, 51 (4): 1689], it is found that there are a large number of borides of different forms growing inside the joint after holding at 1200℃ for 4h. Chai L et al. used B-containing foil (intermediate layer material) to connect DD5 single crystal superalloys [Chai L, et al. J. Mater. Eng. Perform., 2015, 24 (6): 2287], it is found that the borides existing in the joint seriously affect the mechanical properties of single crystal superalloys after holding at 1240℃ for 0.25-4h, the stress-rupture life at 1100℃ / 123MPa is less than 20h, and these borides need to be held for at least 10h or more to eliminate. Therefore, it is of great significance to develop a new type of repair material without B and other melting elements and the corresponding repair process. SUMMARY
[0004] The purpose of the present application is to overcome the problems of poor high-temperature mechanical properties of the repair area in the current brazing type repair method for surface defects of superalloys and long composition homogenization time in the transient liquid phase diffusion welding repair method, and the present application proposes a new type of repair method for defect repair by using a mixed powder of Ni-Cr-Si low melting alloy powder and high-temperature alloy base material powder as a repair material and completing rapid in-situ alloying by using the repair material.
[0005] An in-situ alloying brazing repair method for surface defects of high-temperature alloy blades, characterized in that a mixed powder composed of Ni-Cr-Si low melting alloy powder and high-temperature alloy base material powder is used as a repair material, heated to a repair temperature higher than the liquidus of the Ni-Cr-Si alloy and lower than the solidus of the base material powder under vacuum and pressureless conditions, and the liquid Ni-Cr-Si alloy wets the high-temperature alloy base material and fills the gap between defects, and isocally diffuses between the added solid high-temperature alloy powder to achieve composition homogenization, and finally realizes in-situ alloying brazing repair.
[0006] Further, the repair material is mixed by two powders: one is Ni(62-75at.%)-Cr(15-18at.%)-Si(10-20at.%) alloy powder, the particle size is 20-50μm, and the volume ratio in the mixed powder is 70%-95%; the other is the original high-temperature alloy base material powder, the particle size is 20-50μm, and the volume ratio in the mixed powder is 5%-30%.
[0007] Further, the in-situ alloying brazing repair method, characterized in that the specific process includes the following steps: Step 1, surface repair area is cleaned with acid. The surface of the high-temperature alloy to be repaired is cleaned with an ethanol solution of hydrofluoric acid to remove surface oxide film and other impurities, wherein the concentration of the hydrofluoric acid in the ethanol solution is 5vol.%-15vol.%. The surface to be repaired is placed in the prepared ethanol solution of hydrofluoric acid and cleaned under ultrasonic condition for 10-30 min at a temperature of 30-50℃; the high-temperature alloy to be repaired after cleaning is placed in a high-purity ethanol solution and repeatedly cleaned with ultrasonic for 2-4 times, each time for 10-20 min; after cleaning, the high-temperature alloy to be repaired is dried in a vacuum drying oven, the drying temperature is 40-60℃ and the drying time is 10-30 min.
[0008] Step 2, prepositioning of repair material. The Ni-Cr-Si alloy powder and the high-temperature alloy base material powder are weighed according to the proportion, uniformly mixed by mechanical method, and then dropped into an appropriate amount of alpha terpineol (binder) to form a paste; the paste-like repair material is prepositioned on the high-temperature alloy repair area after cleaning.
[0009] Step 3, in-situ alloying brazing repair. The high-temperature alloy prepositioned with the repair material is placed in a vacuum brazing furnace, vacuumed to 3-5×10-3Pa, then heated to 1150-1200℃ at a heating rate of 10-15℃ / min, and held for 30-120 min, and then cooled in the furnace to obtain a high-temperature alloy repair part.
[0010] The present application has the following advantages: 1) The required repair temperature is relatively low, and the influence on the microstructure and properties of the high-temperature alloy base material is small; 2) Compared with the traditional brazing, the composition of the repair area is similar to that of the base material, the heat-resistant temperature is high, and the high-temperature mechanical properties are good; 3) Compared with the transient liquid phase diffusion welding method, the composition of the repair area is more uniform, and the process belongs to a large-area, short-distance rapid diffusion mechanism, and the required holding time is short; 4) The proportion of high and low melting powders in the repair material can be adjusted, and by adjusting the proportion of the high-temperature alloy base material powder, both small-size crack repair and large-size crack and etch pit brazing repair can be achieved. BRIEF DESCRIPTION OF DRAWINGS
[0011] Figure 1 Macroscopic morphology of the Ni-Cr-Si alloy powder in the repair material.
[0012] Figure 2 Microstructure of the in-situ alloying brazing repair area of the surface defect of the DD413 single-crystal high-temperature alloy (Example 1).
[0013] Figure 3 Microstructure of the in-situ alloying brazing repair area of the surface defect of the K640 cobalt-based high-temperature alloy (Example 3).
[0014] Figure 4 Microstructure of in-situ alloying brazing repaired region of surface defect of DD413 single crystal superalloy (comparative example 2).
[0015] Figure 5 Microstructure of in-situ alloying brazing repaired region of surface defect of K640 cobalt-based superalloy (comparative example 4). DETAILED DESCRIPTION
[0016] Example 1
[0017] This example is a kind of DD413 single crystal superalloy surface crack in-situ alloying brazing repair material and method.
[0018] The superalloy involved is DD413 single crystal superalloy, and the surface pre-crack size is 6 mm long, 0.2 mm wide and 1 mm deep. The repair material involved is a mixed powder of Ni-Cr-Si alloy powder and DD413 superalloy powder, wherein the Ni-Cr-Si alloy powder has a composition of Ni61.97at.%, Cr18.09at.%, Si19.94at.% and a particle size of 20-30μm; the DD413 superalloy powder has a particle size of 20-30μm and accounts for 10vol.% in the mixed powder.
[0019] The specific repair process of this example includes the following steps: Step 1, pickling the surface repair area. The to-be-repaired area of DD413 single crystal superalloy is cleaned with a hydrofluoric acid ethanol solution to remove surface oxidation film and other impurities, wherein the concentration of hydrofluoric acid in the ethanol solution is 5vol.%. The to-be-repaired area is placed in the prepared hydrofluoric acid ethanol solution and pickled under ultrasonic conditions for 30min at a temperature of 40℃; the pickled superalloy repair area is placed in a high-purity ethanol solution and repeatedly cleaned with ultrasonic waves for 2 times, each time for 10min; after cleaning, it is placed in a vacuum drying oven for drying, the drying temperature is 40℃ and the drying time is 10min.
[0020] Step 2, prepositioning repair material. The Ni-Cr-Si alloy powder and DD413 single crystal superalloy base material powder are weighed according to the proportion, mixed uniformly by mechanical method, and then a proper amount of alpha terpineol is added to make a paste; the paste-like repair material is prepositioned on the superalloy repair area after pickling.
[0021] Step 3, in-situ alloying brazing repair. The superalloy with prepositioned repair material is placed in a vacuum brazing furnace, vacuumed to 5×10-3Pa, then heated to 1175℃ at a rate of 15℃ / min, and cooled by furnace cooling after holding for 60min to obtain a superalloy repair piece.
[0022] First, the macroscopic morphology of the joint obtained in step 3 was analyzed; then, it was cut along the axial section, and the interface was successively polished with sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000 to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. Figure 2 As shown. X-ray diffraction and energy dispersive spectroscopy (EDS) were used to identify the phase composition. Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture and subjected to room temperature and 850℃ high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results show that the average room temperature tensile strength of the repair area is 846.5 MPa, reaching 84.1% of the room temperature tensile strength of the base material (1007 MPa); the average 850℃ tensile strength is 734 MPa, reaching 79.7% of the 850℃ tensile strength of the base material (921 MPa). Compared with the traditional instantaneous liquid phase diffusion welding repair method, which requires tens of hours of heat preservation, the in-situ alloying brazing repair method involved in this embodiment significantly shortens the repair time (60 min).
[0023] Example 2
[0024] This embodiment describes an in-situ alloying brazing repair material and method for surface cracks in DD413 single-crystal high-temperature alloy.
[0025] The high-temperature alloy involved is DD413 single-crystal high-temperature alloy, with a pre-existing surface crack size of 6 mm in length, 0.2 mm in width, and 1 mm in depth. The repair material involved is a mixture of Ni-Cr-Si alloy powder and DD413 high-temperature alloy powder. The Ni-Cr-Si alloy powder composition is Ni 66.79 at.%, Cr 17.00 at.%, Si 16.21 at.%, with a particle size of 20–30 μm; the DD413 high-temperature alloy powder has a particle size of 20–30 μm and accounts for 15 vol.% of the mixture.
[0026] The specific repair process in this embodiment includes the following steps: Step 1: Acid pickling of the repaired area. The area to be repaired on the DD413 single-crystal superalloy is cleaned with a hydrofluoric acid-ethanol solution to remove surface oxide films and other impurities. The concentration of hydrofluoric acid in the ethanol solution is 10 vol.%. The area to be repaired is placed in the prepared hydrofluoric acid-ethanol solution and acid-washed under ultrasonic conditions for 30 minutes at 40°C. After acid pickling, the superalloy repaired area is placed in a high-purity ethanol solution and repeatedly cleaned ultrasonically twice, each time for 10 minutes. After cleaning, it is placed in a vacuum drying oven to dry for 10 minutes at 40°C.
[0027] Step 2, Pre-place the repair material. Weigh out Ni-Cr-Si alloy powder and DD413 single crystal high-temperature alloy base powder according to the ratio, mix them evenly by mechanical means, and then add an appropriate amount of α-terpineol to make a paste; pre-place the paste repair material on the high-temperature alloy repair area after acid washing.
[0028] Step 3, in-situ alloying brazing repair. The high-temperature alloy pre-filled with repair material is placed in a vacuum brazing furnace, evacuated to 5×10-3 Pa, then heated to 1200℃ at a heating rate of 15℃ / min, held at that temperature for 120 min, and then cooled in the furnace to obtain the high-temperature alloy repaired part.
[0029] First, the macroscopic morphology of the joint obtained in step 3 was analyzed. Then, it was cut along the axial section, and the interface was successively polished with sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000 to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. The phase composition was identified by X-ray diffraction and energy dispersive spectroscopy. Tensile specimens were prepared using the same materials and processes. The resulting joint was placed in a special fixture and subjected to room temperature and 850℃ high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results showed that the average tensile strength of the repaired area at room temperature was 817.5 MPa, reaching 81.2% of the room temperature tensile strength of the base material (1007 MPa); the average tensile strength at 850℃ was 389.5 MPa, reaching 41.4% of the 850℃ tensile strength of the base material (921 MPa). Compared with the traditional instantaneous liquid phase diffusion welding repair method, which requires a holding time of tens of hours, the in-situ alloying brazing repair method involved in this embodiment significantly shortens the repair time (120 min).
[0030] Example 3
[0031] This embodiment describes an in-situ alloying brazing repair material and method for surface cracks in K640 cobalt-based high-temperature alloys.
[0032] The high-temperature alloy involved is K640 cobalt-based high-temperature alloy, with a pre-existing surface crack measuring 6 mm in length, 0.2 mm in width, and 1 mm in depth. The repair material is a mixture of Ni-Cr-Si alloy powder and K640 cobalt-based high-temperature alloy powder. The Ni-Cr-Si alloy powder composition is 61.97 at.%, 18.09 at.%, and 19.94 at.%, with a particle size of 20–30 μm; the K640 high-temperature alloy powder has a particle size of 20–30 μm and accounts for 10 vol.% of the mixture.
[0033] The specific repair process in this embodiment includes the following steps: Step 1: Acid pickling of the repaired area. The area to be repaired on the K640 cobalt-based superalloy is cleaned with an ethanol solution of hydrofluoric acid to remove surface oxide films and other impurities. The concentration of hydrofluoric acid in the ethanol solution is 5 vol.%. The area to be repaired is placed in the prepared hydrofluoric acid-ethanol solution and acid-washed under ultrasonic conditions for 30 minutes at 40°C. After acid pickling, the superalloy repaired area is placed in a high-purity ethanol solution and repeatedly cleaned ultrasonically twice, each time for 10 minutes. After cleaning, it is placed in a vacuum drying oven to dry for 10 minutes at 40°C.
[0034] Step 2, Pre-place the repair material. Weigh out Ni-Cr-Si alloy powder and K640 cobalt-based high-temperature alloy base powder according to the ratio, mix them evenly by mechanical means, and then add an appropriate amount of α-terpineol to make a paste; pre-place the paste repair material on the high-temperature alloy repair area after acid pickling.
[0035] Step 3, in-situ alloying brazing repair. The high-temperature alloy pre-filled with repair material is placed in a vacuum brazing furnace, the vacuum is drawn to 5×10-3 Pa, and then heated to 1175℃ at a heating rate of 15℃ / min. After holding at this temperature for 60 minutes, the furnace is cooled to obtain the high-temperature alloy repaired part.
[0036] First, the macroscopic morphology of the joint obtained in step 3 was analyzed; then, it was cut along the axial section, and the interface was successively polished with sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000 to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. Figure 3 As shown. X-ray diffraction and energy dispersive spectroscopy (EDS) were used to identify the phase composition. Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture and subjected to room temperature and 850℃ high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results show that the average room temperature tensile strength of the repair area is 443 MPa, reaching 82.2% of the room temperature tensile strength of the base material (539 MPa); the average 850℃ tensile strength is 274 MPa, reaching 86.8% of the 850℃ tensile strength of the base material (315.5 MPa). Compared with the traditional instantaneous liquid phase diffusion welding repair method, which requires tens of hours of heat preservation, the in-situ alloying brazing repair method involved in this embodiment significantly shortens the repair time (60 min).
[0037] Example 4
[0038] This embodiment describes an in-situ alloying brazing repair material and method for surface cracks in K640 cobalt-based high-temperature alloys.
[0039] The high-temperature alloy involved is K640 cobalt-based high-temperature alloy, with a pre-existing surface crack measuring 6 mm in length, 0.2 mm in width, and 1 mm in depth. The repair material is a mixture of Ni-Cr-Si alloy powder and K640 high-temperature alloy powder. The Ni-Cr-Si alloy powder composition is Ni 66.79 at.%, Cr 17.00 at.%, and Si 16.21 at.%, with a particle size of 20–30 μm. The K640 cobalt-based high-temperature alloy powder, with a particle size of 20–30 μm, accounts for 15 vol.% of the mixture.
[0040] The specific repair process in this embodiment includes the following steps: Step 1: Acid pickling of the repaired area. The area to be repaired on the K640 cobalt-based superalloy is cleaned with a hydrofluoric acid-ethanol solution to remove surface oxide films and other impurities. The concentration of hydrofluoric acid in the ethanol solution is 10 vol.%. The area to be repaired is placed in the prepared hydrofluoric acid-ethanol solution and acid-washed under ultrasonic conditions for 30 minutes at 40°C. After acid pickling, the superalloy repaired area is placed in a high-purity ethanol solution and repeatedly cleaned ultrasonically twice, each time for 10 minutes. After cleaning, it is placed in a vacuum drying oven to dry for 10 minutes at 40°C.
[0041] Step 2, Pre-place the repair material. Weigh out Ni-Cr-Si alloy powder and K640 cobalt-based high-temperature alloy base powder according to the ratio, mix them evenly by mechanical means, and then add an appropriate amount of α-terpineol to make a paste; pre-place the paste repair material on the high-temperature alloy repair area after acid pickling.
[0042] Step 3, in-situ alloying brazing repair. The high-temperature alloy pre-filled with repair material is placed in a vacuum brazing furnace, evacuated to 5×10-3 Pa, then heated to 1200℃ at a heating rate of 15℃ / min, held at that temperature for 120 min, and then cooled in the furnace to obtain the high-temperature alloy repaired part.
[0043] First, the macroscopic morphology of the joint obtained in step 3 was analyzed. Then, it was cut along the axial section, and the interface was successively polished with sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000 to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. The phase composition was identified by X-ray diffraction and energy dispersive spectroscopy. Tensile specimens were prepared using the same materials and processes. The resulting joint was placed in a special fixture and subjected to room temperature and 850℃ high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results show that the average tensile strength of the repaired area at room temperature is 331 MPa, reaching 61.4% of the tensile strength of the base material at room temperature (539 MPa); the average tensile strength at 850℃ is 261 MPa, reaching 82.7% of the tensile strength of the base material at 850℃ (315.5 MPa). Compared with the traditional instantaneous liquid phase diffusion welding repair method, which requires tens of hours of heat preservation, the in-situ alloying brazing repair method involved in this embodiment significantly shortens the repair time (120 min).
[0044] Comparative Example 1
[0045] The only difference between Comparative Example 1 and Example 1 is that, in terms of atomic fraction, the repair material involved is a Ni-Cr-Si alloy powder composed of 59% Ni, 18.5% Cr, and 22.5% Si.
[0046] Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture, and tensile strength tests were conducted at room temperature and 850°C on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repaired area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results showed that the average room temperature tensile strength of the repaired area was 526.3 MPa, reaching 52.3% of the room temperature tensile strength of the base material (1007 MPa); the average tensile strength at 850°C was 280 MPa, reaching 30.4% of the 850°C tensile strength of the base material (921 MPa). Compared with Example 1, the room temperature tensile strength and 850°C tensile strength of the repaired area were significantly reduced when using the repair material in Comparative Example 1.
[0047] Comparative Example 2
[0048] The only difference between Comparative Example 2 and Example 2 is that the volume fraction of DD413 high-temperature alloy base powder in the repair material involved is 35%.
[0049] The repair area was cut along the axial section, and the interface was successively polished using sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000, to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. Figure 4 As shown. Compared with Example 2, when the amount of DD413 high-temperature alloy powder added to the repair material was too high, a large number of pores appeared in the repair area. X-ray diffraction and energy dispersive spectroscopy were used to identify the phase composition. Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture and subjected to room temperature and 850°C high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results showed that the average room temperature tensile strength of the repair area was 459 MPa, reaching 45.6% of the room temperature tensile strength of the base material (1007 MPa); the average 850°C tensile strength was 328 MPa, reaching 35.6% of the 850°C tensile strength of the base material (921 MPa).
[0050] Comparative Example 3
[0051] The only difference between Comparative Example 3 and Example 4 is that the volume fraction of K640 cobalt-based superalloy base powder in the repair material involved is 32%.
[0052] The repair area was cut along the axial section, and the interface was successively polished using sandpaper of grits 240, 400, 600, 800, 1000, 1200, 1500, and 2000, to prepare a metallographic sample. The microstructure of the joint was observed using a scanning electron microscope. Figure 5As shown. Compared with Example 4, when the amount of K640 cobalt-based superalloy powder added to the repair material was too high, obvious porosity appeared in the repair area. X-ray diffraction and energy dispersive spectroscopy were used to identify the phase composition. Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture and subjected to room temperature and 850°C high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded. The tensile strength of the repair area (joint) was calculated based on the maximum load, and the average strength of the three specimens was taken as the final result. The results showed that the average room temperature tensile strength of the repair area was 273 MPa, reaching 50.6% of the room temperature tensile strength of the base material (539 MPa); the average 850°C tensile strength was 186 MPa, reaching 58.9% of the 850°C tensile strength of the base material (315.5 MPa). This is because the repair material in this method consists of two parts: low-melting-point Ni-Cr-Si alloy powder and high-melting-point high-temperature alloy base powder. During the repair process, the low-melting-point Ni-Cr-Si alloy powder melts to form a liquid phase, while the high-melting-point alloy base powder remains in the solid phase. If an excessive amount of high-melting-point high-temperature alloy base powder is added to the repair material, the proportion of liquid phase in the repair zone decreases while the proportion of solid phase increases. This can easily lead to insufficient liquid phase filling in the repair zone, resulting in a large number of void defects. These defects will simultaneously affect the room temperature and high-temperature tensile properties of the repair zone.
[0053] Comparative Example 4
[0054] The only difference between Comparative Example 4 and Example 1 is that the repair temperature is 1100°C.
[0055] Observations revealed that when the repair temperature was 1100℃, the repair material did not completely melt, resulting in poor macroscopic formation of the repair area and obvious void defects within the repair area. Tensile specimens were prepared using the same materials and processes. The resulting joints were placed in a special fixture and subjected to room temperature and 850℃ high-temperature tensile strength tests on an electronic universal testing machine. The maximum load output when the workpiece broke was recorded, and the tensile strength of the repair area (joint) was calculated based on the maximum load. The average strength of the three specimens was taken as the final result. The results showed that the average room temperature tensile strength of the repair area was 201 MPa, only 19.9% of the room temperature tensile strength of the base material (1007 MPa); the average 850℃ tensile strength was 183 MPa, reaching 19.8% of the 850℃ tensile strength of the base material (921 MPa). Compared with Example 1, when the repair temperature was too low, the formability of the repair area was poor, and both the room temperature tensile strength and the 850℃ high-temperature tensile strength were low. Furthermore, repair temperatures above 1215℃ exceed the solution treatment temperature of this single-crystal superalloy, and repairs performed at this temperature will adversely affect the microstructure and properties of the superalloy base material. Taking all factors into consideration, a repair temperature between 1150℃ and 1200℃ is most suitable.
[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for in-situ alloying brazing repair of surface defects on high-temperature alloy blades, characterized in that, A mixed powder consisting of Ni-Cr-Si low-melting alloy powder and high-temperature alloy base material powder is used as the repair material. Under vacuum and pressureless conditions, it is heated to a repair temperature higher than the liquidus line of Ni-Cr-Si alloy but lower than the solidus line of the base material powder. The liquid Ni-Cr-Si alloy wets the high-temperature alloy base material and fills the defect gaps. At the same time, isothermal liquid-solid diffusion occurs between the liquid Ni-Cr-Si alloy and the added solid high-temperature alloy powder to achieve composition homogenization, and finally realize in-situ alloying brazing repair.
2. The in-situ alloying brazing repair method for surface defects of high-temperature alloy blades as described in claim 1, characterized in that, The repair material is composed of two powders: one is a Ni (62-75 at.%)-Cr (15-18 at.%)-Si (10-20 at.%) alloy powder with a particle size of 20-50 μm, accounting for 70%-95% of the volume of the mixed powder; the other is the original high-temperature alloy base powder with a particle size of 20-50 μm, accounting for 5%-30% of the volume of the mixed powder.
3. The in-situ alloying brazing repair method for surface defects of high-temperature alloy blades as described in claim 1, characterized in that, The specific process includes the following steps: Step 1: Pickling the surface repair area. The high-temperature alloy area to be repaired is cleaned with an ethanol solution of hydrofluoric acid to remove surface oxide film impurities. The concentration of hydrofluoric acid in the ethanol solution is 5 vol.%–15 vol.%. The area to be repaired is placed in the prepared hydrofluoric acid-ethanol solution and pickled under ultrasonic conditions for 10–30 minutes at a temperature of 30–50°C. After pickling, the high-temperature alloy repair area is placed in a high-purity ethanol solution and repeatedly cleaned ultrasonically 2–4 times, each time for 10–20 minutes. After cleaning, it is placed in a vacuum drying oven to dry for later use at a temperature of 40–60°C for 10–30 minutes. Step 2: Pre-place the repair material. Weigh out Ni-Cr-Si alloy powder and high-temperature alloy base material powder according to the ratio, mix them evenly by mechanical means, and then add an appropriate amount of α-terpineol as a binder to make a paste. Place the paste-like repair material into the high-temperature alloy repair area after acid pickling. Step 3, in-situ alloying brazing repair: The high-temperature alloy pre-filled with repair material is placed in a vacuum brazing furnace, and the vacuum is drawn to 3 to 5 × 10-3 Pa. Then it is heated to 1150 to 1200℃ at a heating rate of 10 to 15℃ / min. After holding at this temperature for 30 to 120 minutes, the furnace is cooled to obtain the high-temperature alloy repaired part.